The Influence of parental attention and interest in learning on the ability to read The Qur'an in: Study in TPQ Al-Istiqomah - Sarif, Reza; An-Naafi, Ummu Syabrina; Whindari, Yayuk (Maliki Interdisciplinary Journal, 2024)
Studying the Koran is mandatory for Muslims. The Koran is the main source of Islamic education whose existence greatly influenced the educational system of the Prophet Muhammad SAW and his companions. Apart from that, the Qur'an also contains specific and fascinating educational concepts so that it can form individuals who believe and always glorify Allah and believe in the last day. TPQ Al-Istiqomah is an Al-Qur'an educational institution located in Wiloso Hamlet, Gondowangi Village, Wagir District, Malang Regency. This institution accepts students from various circles, from kindergarten (TK) to SMP/MTs. In this area, especially in Wiloso Hamlet, most people work as factory workers. This causes them to have less time to teach or motivate their children to learn to read the Koran. This research aims to determine the influence of parental attention and student interest on the ability to read the Koran at TPQ Al-Istiqomah through quantitative research methods. The research results show that there is a significant influence of the variables of parental attention and student interest on the ability to read the Koran at TPQ Al - Al-Istiqomah. This is proven by the partial test (T-test) results of each variable with a sig value <0.05. Meanwhile, the simultaneous test (F test) results show a sig value <0.005, namely 0.000. This data shows that parental attention and students' interests have a simultaneous and significant influence on the ability to read the Al-Qur'an in TPQ Al-Istiqomah students.